2017
DOI: 10.1074/jbc.m117.818146
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear export factor 3 regulates localization of small nucleolar RNAs

Abstract: Small nucleolar RNAs (snoRNAs) guide chemical modifications of ribosomal and small nuclear RNAs, functions that are carried out in the nucleus. Although most snoRNAs reside in the nucleolus, a growing body of evidence indicates that snoRNAs are also present in the cytoplasm and that snoRNAs move between the nucleus and cytoplasm by a mechanism that is regulated by lipotoxic and oxidative stress. Here, in a genome-wide shRNA-based screen, we identified nuclear export factor 3 (NXF3) as a transporter that alters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Phenotype-driven forward genetic screens have advanced our understanding of the regulation of cellular responses to lipid overload in mammalian cells. Such approaches rely on random disruption of genetic loci or knockdown, followed by positive selection of cells that survive better under lipotoxic conditions or by negative selection of cells that have enhanced sensitivity to lipotoxicity (24,35,42,43). Genetic disruptions achieved by short hairpin RNA, siRNA, and CRISPR are typically designed to target open reading frames.…”
Section: Rounding Up New Suspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotype-driven forward genetic screens have advanced our understanding of the regulation of cellular responses to lipid overload in mammalian cells. Such approaches rely on random disruption of genetic loci or knockdown, followed by positive selection of cells that survive better under lipotoxic conditions or by negative selection of cells that have enhanced sensitivity to lipotoxicity (24,35,42,43). Genetic disruptions achieved by short hairpin RNA, siRNA, and CRISPR are typically designed to target open reading frames.…”
Section: Rounding Up New Suspectsmentioning
confidence: 99%
“…In these cells, levels of all mature intronic snoRNAs are decreased, even though splicing to produce mRNAs remains unperturbed. Second, short hairpin RNA-mediated targeting of nuclear export factor 3 (NXF3) also renders cells resistant to lipotoxic stress (42). The vast majority of snoRNAs are localized to the nucleolus, and lipotoxic stress increases the appearance of snoRNAs in the cytoplasm (54).…”
Section: Rounding Up New Suspectsmentioning
confidence: 99%
“…snoRNAs are a type of linear transcripts with protein-guiding function. Depending on their sequence characteristics, the snoRNAs are divided into C/D snoRNA, H/ACA snoRNA, and U snoRNA [ 116 , 117 ]. The C/D snoRNA and the H/ACA snoRNA are transcribed from protein-coding genes, as primary mRNAs.…”
Section: The Small Nucleolar Rnasmentioning
confidence: 99%
“…Then the 3’ and the 5’ end are shortened by the local endonucleases, until the mature C/D or H/ACA snoRNA is generated. The U3, U8 and U13 snoRNAs are transcribed from the promoter regions of RNA Pol II [ 116 ].…”
Section: The Small Nucleolar Rnasmentioning
confidence: 99%
“…This redistribution of snoRNAs depends on superoxide and NADPH oxidase activity and does not simply result from compromise of the nuclear compartment. We also recently found that nuclear export factor 3 (NXF3) regulates the trafficking of snoRNAs between the nucleus and cytosol (11). Importantly, regulated appearance of snoRNAs in the cytoplasm raises the possibility of novel functions for snoRNAs outside the nucleus.…”
mentioning
confidence: 99%